2013
DOI: 10.1163/22134808-000s0091
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of sound in determining the perceptual upright

Abstract: The perceived direction of up depends on visual, gravity, and body cues, each of which is given a weighting by the brain (Dyde et al., 2006). Little work has been done, however, to demonstrate whether sound might also be usable by the brain as a cue to up. Here we assess the possible contribution of sound to perceived orientation by adding a sound cue to gravity. The perceptual upright, the direction in which a character is most easily recognized, was assessed using the Oriented Character Recognition Test (OCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…But is this elevation defined in head or space coordinates? We showed that such sounds were perceived as lying on an axis defined neither by the head nor gravity but rather that lined up with the perceptual upright ( Carnevale and Harris, 2013 ). Non-spatial sounds (tones played through headphones) that differed only in their frequency content (either rising or falling frequencies) were presented while observers viewed ambiguous visual motion in either the horizontal or vertical directions created by superimposing two gratings moving in opposite directions (left and right or up and down; Figure 3 ).…”
Section: Introductionmentioning
confidence: 92%
“…But is this elevation defined in head or space coordinates? We showed that such sounds were perceived as lying on an axis defined neither by the head nor gravity but rather that lined up with the perceptual upright ( Carnevale and Harris, 2013 ). Non-spatial sounds (tones played through headphones) that differed only in their frequency content (either rising or falling frequencies) were presented while observers viewed ambiguous visual motion in either the horizontal or vertical directions created by superimposing two gratings moving in opposite directions (left and right or up and down; Figure 3 ).…”
Section: Introductionmentioning
confidence: 92%